New species of the genus Gynaecoserica Brenske, 1896 from Indochina (Coleoptera: Scarabaeidae: Sericini) - Ahrens, Dirk (Zootaxa, 2021)
Here I describe five additional new species of Gynaecoserica Brenske, 1896 from Indochina: Gynaecoserica bihtanensis Ahrens, new species (from Myanmar), G. fallaciosa Ahrens, new species , G. feresimplex Ahrens, new species, G. pseudocymosa Ahrens, new species (all from Thailand), G. ottoi Ahrens, new species (from Laos). The male genitalia of the new species are illustrated.